Does female unemployment increase crime ? Evidence in selected Sub-Saharan African countries: Array - Ayang, Eric; MELA , Christel; FOSSONG, Derrick (EuroEconomica, 2022)
A large body of theorical and empirical researches suggest that unemployment has a positive and significant effect on crime. Contrary to this finding, some studies conclude that unemployment has a negative effect on crime. There further revealed that there is mixed relationship between unemployment and crime. In this context, this paper examines the direct effect of female unemployment on crime in a sample of 40 Sub-Saharan African countries over the period 1990-2020. Using non-parametric and parametric methods. The paper disclosed a positive relationship between female unemployment and crime. The econometric analysis suggests that a higher level of female unemployment increase crime.